2017
DOI: 10.21548/8-2-2312
|View full text |Cite
|
Sign up to set email alerts
|

Population Dynamics of the Root-knot Nematodes Meloidogyne incognita (Kofoid & White) Chitwood and M. javanica (Treub) Chitwood on Grapevines in two different Regions of South Africa

Abstract: Two root-knot nematode species, Me/oidogyne incognita and M.javanica, were studied with regard to their seasonal population fluctuations on grapevines growing in two vastly different climatic areas. Regular observations on reproduction and numbers of larvae in the soil were compared with patterns of root growth, soil temperature and moisture.Population fluctuations of the two species showed similar trends in spite of the climatic differences in the two areas, but M. incognita in the northern Cape reached highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Daramola et al (2020) reported M. javanica and M. hapla from honeybush fields in Western Cape. According to Loubser and Meyer (1987), the presence of the two most important species in South Africa vineyards is determined by the vastly different climatic regions concerned. The results of the study showed that M. hapla was more prevalent in the sampled honeybush plantations in the Western Cape.…”
Section: Discussionmentioning
confidence: 99%
“…Daramola et al (2020) reported M. javanica and M. hapla from honeybush fields in Western Cape. According to Loubser and Meyer (1987), the presence of the two most important species in South Africa vineyards is determined by the vastly different climatic regions concerned. The results of the study showed that M. hapla was more prevalent in the sampled honeybush plantations in the Western Cape.…”
Section: Discussionmentioning
confidence: 99%
“…Root-knot nematodes (Heteroderidae) have a wide host range, are widely distributed in agricultural soils, and can cause extensive loss in terms of the yield quality of numerous crops (Kleynhans et al, 1996). Damage symptoms on rootknot nematode-infested vines include stunted growth, poor vigour and substandard yields (Loubser & Meyer, 1987).…”
Section: Figure 2 Slashing Of Crops With Slasher (A) Texture Of Slasmentioning
confidence: 99%
“…This is when active root growth starts taking place and soil populations of root-knot nematodes peak in vineyards of the Northern Cape Province (Loubser & Meyer, 1987). Five soil cores were extracted from each of three vines per plot using a soil auger, 30 cm from the vine stem and approximately 30 cm deep.…”
Section: Nematode Samplingmentioning
confidence: 99%